Guillain-Barré - Jennifer Yee, DO; Andrew M King, MD; Jeremiah Emerson, MD (eScholarship Publishing, University of California, 2018)
Audience: This scenario was developed to educate emergency medicine residents on the diagnosis and management of Guillain-Barré syndrome in the emergency department. The case is also appropriate for senior medical students and advanced practice providers. The principles of crisis resource management, teamwork, and communication are also incorporated into the case. Introduction: Patients presenting with suspected Guillain-Barré syndrome require a thorough neurologic exam and likely a lumbar puncture. Due to the ascending weakness that may involve the diaphragm, providers must continually reassess the patient's respiratory and hemodynamic status. If a patient demonstrates respiratory function weakness or has subjective worsening dyspnea, they should be evaluated for intubation. Objectives: At the conclusion of the simulation session, learners will be able to: 1) Recognize the clinical signs and symptoms associated with Guillain-Barré syndrome, including muscle weakness and hyporeflexia. 2) Identify abnormal vital signs secondary to dysautonomia. 3) Discuss evaluation for impending respiratory failure, including bedside pulmonary function testing. 4) Discuss the management of Guillain-Barré, including management of dysautonomia and respiratory failure, as well as definitive management with plasmapheresis versus intravenous immunoglobulin. 5) Appropriately disposition the patient to the intensive care unit. 6) Effectively communicate with team members and nursing staff during resuscitation of a critically ill patient Method: This session was conducted using high-fidelity simulation, followed by a debriefing session and lecture on the diagnosis and management of Guillain-Barré syndrome. Debriefing methods may be left to the discretion of participants, but the authors have utilized advocacy-inquiry techniques. Topics: Medical simulation, Guillain-Barré syndrome, emergency medicine, neurology